Advanced exercise endocrinology - Borer, Katarina T. (Advanced exercise physiology series, 2013)
Advanced Exercise Endocrinology presents a comprehensive examination of the relationship between physical activity and hormone function. As the newest addition to Human Kinetics' Advanced Exercise Physiology Series, this resource offers the most up-to-date information on the quickly advancing field of exercise endocrinology. Written by leading exercise endocrinologist Katarina Borer, Advanced Exercise Endocrinology is an essential reference for exercise physiologists, physiotherapists, and other health professionals researching the connections between exercise, hormone function, and health. Advanced Exercise Endocrinology explains how the human body responds to exercise in order to support the increased energy demand. Readers will explore topics including body fluid balance during exercise and at rest, endocrine and autonomic control of cardiorespiratory function, hormonal control of energy expenditure, and the role of reproductive hormones in exercise. The text offers an integrative perspective and includes the following unique features: An emphasis on the effects of hormones during exercise in the context of biological functions or physiological events to help readers appreciate the complexity of hormonal response from a functional, whole-body perspective; A discussion of hormone actions in exercise with an emphasis on the mechanisms of action, which is key to developing an advanced understanding of metabolism and somatic and physiological adaptations to training; A chapter that brings together research on nonhormonal signaling in exercise, a topic not often presented in a comprehensive manner; An introduction to the principles of hormone measurements, which will be especially helpful to students considering a future in research. Combining foundational concepts and research, this text offers engaging and accessible coverage of this advanced field of study. Chapter summaries help readers focus on the most significant issues presented for each topic, and extensive illustrations, figures, and graphs provide visual reinforcement of key concepts and important research findings. Special sidebars highlight analyses of interesting research findings and practical applications. In examining current research, readers will be able to identify emerging topics and possible directions for future exploration. While the connection between exercise, hormones, and health is well acknowledged, the field had yet to be fully explored. Advanced Exercise Endocrinology will help students and professionals from many health fields better understand how interactions between physical activity and hormone action work to maintain health, improve exercise performance, and prevent metabolic disabilities. Human Kinetics' Advanced Exercise Physiology Series offers books for advanced undergraduate and graduate students as well as professionals in exercise science and kinesiology. These books highlight the complex interaction of various systems both at rest and during exercise. Each text in this series offers a clear and concise explanation of the system and details how each is affected by acute exercise and chronic exercise training. Advanced Exercise Endocrinology is the fourth volume in the series.